D-Space, makerspace, and hackerspace in cyberspace: Cybersecurity strategies for digital preservation of library resources in the post-Covid-19 pandemic - Ismail Adakawa, Murtala (Advanced Notes in Information Science, 2023)
This paper explores the status of d-space in the milieu of makerspace and hackerspace in the cyber domain. These two belligerent sides excel in critical thinking, creativity, collaborations, and communication important for 21st-century skills a consequence of giving rise to difficulty in differentiating one side as an independent entity from the other. Organizations require one as a prerequisite for employment and application of the other in post-education. Covid-19 has consolidated these sides and brought with it many cybersecurity challenges that call for organizations to prepare for hacking activities in the post-pandemic era. It has opened a desire and demand for information at a logarithmic phase at the free of cost in an electronic format like never before. Many works of literature have been reviewed to supply the lack of an accurate sequence of events that shaped the behavior and attitudes of individuals in this era.